Molecular networking and whole-genome analysis aid discovery of an angucycline that inactivates mTORC1/C2 and induces programmed cell death - Dan, Vipin Mohan; Vinodh, J. S.; Sandesh, C. J.; Sanawar, Rahul; Lekshmi, Asha; Kumar, R. Ajay; Kumar, T. R. Santhosh; Marelli, Uday Kiran; Dastager, Syed G.; Pillai, M. Radhakrishna (ACS Chemical Biology, 2020)
Rediscovery of known compounds and time consumed in identification, especially high molecular weight compounds with complex structure, have let down interest in drug discovery. In this study, whole-genome analysis of microbe and Global Natural Products Social (GNPS) molecular networking helped in initial understanding of possible compounds produced by the microbe. Genome data revealed 10 biosythethic gene clusters that encode for secondary metabolites with anticancer potential. NMR analysis of the pure compound revealed the presence of a four-ringed benz[a]anthracene, thus confirming angucycline; molecular networking further confirmed production of this class of compounds. The type II polyketide synthase gene identified in the microbial genome was matched with the urdamycin duster by BLAST analysis. This information led to ease in identification of urdamycin E and a novel natural derivative, urdamycin V, purified from Streptomyces sp. OA293. Urdamycin E (Urd E) induced apoptosis and autophagy in cancer cell lines. Urd E exerted anticancer action through inactivation of the mTOR complex by preventing phosphorylation at Ser 2448 and Ser 2481 of mTORC1 and mTORC2, respectively. Significant reduction in phosphorylation of the major downstream regulators of both mTORC1 (p70s6k and 4e-bp1) and mTORC2 (Akt) were observed, thus further confirming complete inhibition of the mTOR pathway. Urd E presents itself as a novel mTOR inhibitor that employs a novel mechanism in mTOR pathway inhibition.